The pollination ecology of commercial sunflower (Helianthus annuus L.) in South Africa with special reference to the honeybee (Apis mellifera L.) - Holm, E. (University of Pretoria, 2013)
Dissertation (MSc (Entomology))--University of Pretoria, 1988.